DETERMINANTS OF INITIAL RETURN PERFORMANCE IN INDONESIA INITIAL PUBLIC OFFERINGS: A 2018-2022 ANALYSIS - Syaifuddin, Nabilah; Rizkianto, Eko (Universitas Muhammadiyah Tangerang, 2024)
This research aims to analyze the impact of firm age, IPO risk, underwriter reputation, auditor reputation, company’s industry, Altman Z-Score, firm size, and intended use of IPO proceeds on the level of initial returns of IPOs. In this study, the intended use of IPO proceeds is categorized into growth opportunities, debt repayment, and working capital. The sample for this study consists of companies listed on the Indonesia Stock Exchange during the period of 2018-2022. In addition to the Ordinary Least Square test, the regression method with Quantile Regression is used to analyze the effects in the model at different quantile levels. Overall, IPO risk, Altman Z-Score, total assets, and growth opportunities have a positive influence on the level of initial returns of IPOs. Furthermore, underwriter reputation, auditor reputation, company’s industry, debt repayment, and working capital have a negative influence on the level of initial returns on the Indonesia Stock Exchange. On the other hand, firm age does not have a significant effect on the level of initial returns in the Indonesian capital market.